An aggregation-induced emission dye-powered afterglow luminogen for tumor imaging - Xu, Yan (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Semiconducting polymer (SP)-based afterglow luminogens are showing increasing potential for in vivo imaging because of their long-life luminescence and the associated benefits (e.g., zero-autofluorescence background and high signal-to-noise ratio). However, such organic afterglow luminescence agents are still rare and their application is usually limited by their relatively low afterglow intensity and short afterglow duration. Herein, we report an aggregation-induced emission (AIE) dye-powered SP afterglow luminogen by leveraging on the unique characteristics of an AIE dye to circumvent the concentration-quenching effect, enhance afterglow intensity and prolong afterglow duration. The underlying working mechanism is investigated by a series of experiments and it is found that the AIE dye provides sufficient (1)O(2) to excite SPs and form massive amounts of high-energy intermediates, and then the SP intermediates emit photons that can activate the AIE dye to generate (1)O(2) and simultaneously trigger the energy transfer process between the SPs and AIE dye, resulting in a deep-red emission. It is this closed-loop of “photon–(1)O(2)–SP intermediates–photon” that provides the afterglow emission even after the cessation of the excitation light. The as-prepared luminogen shows good performance in in vivo tumour imaging. This study demonstrates the advantages of AIE-facilitated afterglow luminescence and discloses its mechanism, and hopefully it could inspire the development of other innovative designs for cancer theranostics.